Audit Quality and Tax Aggressiveness: Financial Service Companies Overview - Adegbite, Tajudeen Adejare (Universitas Kristen Maranatha, 2025)
Purpose – The study investigates the effect of audit quality on tax aggressiveness among financial service companies listed in Nigeria from 2014 to 2023. Design/methodology/approach – Data garnered from selected financial service companies’ annual reports were analyzed with correlation analysis and variance inflation factor test to detect multicollinearity while panel data analysis was employed for significant examination. Findings – The findings indicate that audit tenure was found to have a significant positive effect on CASHETR and BTD. Audit fees showed a significant negative effect on CASHETR but positive effect on BTD while audit committee demonstrated a significant positive effect on CASHETR but negative on BTD. It is concluded that there is significant impact of audit quality on tax aggressiveness in listed financial service companies in Nigeria. Research limitations/implications – It is recommended that financial service companies should prioritize engaging high-quality audit firms, maintaining longer audit tenures, and strengthening their audit committees with diverse expertise which will be associated with improved alignment between financial and tax reporting as well as more conservative tax practices. Regulatory bodies should develop comprehensive frameworks that will integrate assessments of audit quality, book-tax differences, and effective tax rates for better identifying potential areas of concern, and guide companies in balancing tax efficiency with compliance and reporting quality. Keywords: Audit Committee, Audit Fees, Audit Tenure, Audit Quality, Book-Tax Differences, Cash Effective Tax Rate, Tax Aggressiveness